Dietary Histidine Supplementation Maintained Amino Acid Homeostasis and Reduced Hepatic Lipid Accumulation of Juvenile Largemouth Bass, Micropterus Salmoides - Hualiang Liang; Gangchun Xu; Pao Xu; Jian Zhu; Songlin Li; Mingchun Ren (Aquaculture Nutrition)
This 56-day research aimed to evaluate the recommended histidine requirement and the influence of dietary histidine levels on the protein and lipid metabolism of juvenile largemouth bass (Mieropterus salmoides). The initial weight of the largemouth bass was 12.33±0.01 g, which was fed with six graded levels of histidine. The results showed that appropriate dietary histidine had a positive effect on growth, with a higher specific growth rate, final weight, weight gain rate, protein efficiency rate, and a lower feed conversion rate and feed intake rate being observed in 1.08-1.48% dietary histidine groups. Furthermore, the mRNA levels of GH, IGF-1, TOR, and S6 showed an increasing trend first and then declined, similar to the trend of the growth and protein content of the whole body composition. Meanwhile, dietary histidine levels could be sensed by the AAR signaling pathway, representing as downregulation of core genes of AAR signaling pathway with the increased dietary histidine levels, including GCN2, eIF2α, CHOP, ATF4, and REDD1. In addition, increased dietary histidine levels decreased the lipid content of the whole body and the liver by upregulating the mRNA levels of core genes of the PPARα signaling pathways, including PPARα, CPT1, L-FABP, and PGC1α. However, increased dietary histidine levels downregulated the mRNA levels of core genes of the PPARγ signaling pathways such as PPARγ, FAS, ACC, SREBP1, and ELOVL2. These findings were also supported by the positive area ratio of hepatic oil red O staining and the TC content of plasma. According to the specific growth rate and feed conversion rate, the recommended histidine requirement of juvenile largemouth bass was 1.26% of the diet (2.68% of dietary protein) by regression lines calculated using a quadratic model. In general, histidine supplementation promoted protein synthesis and lipid decomposition and reduced lipid synthesis by activating the TOR, AAR, PPARα, and PPARγ signaling pathways, which provided a new perspective to solve the fatty liver problem of largemouth bass by nutritional means.